ANALISIS MAKNA PESAN PADA PERTUNJUKAN WAYANG KULIT DALAM PENUMBUHAN NILAI MORAL MASYARAKAT DI PADEPOKAN SEHAT MEDIKA, KEBUMEN - Anjar Mukti (2022)
Shadow puppet show as part of traditional culture does not only function as entertainment with aesthetic value. The Shadow puppet show essentially has a function as a traditional communication medium, which contains both implied and explicit messages. The messages contained in the shadow puppet show generally are about the values of life that can be used as moral growth in the society. The purpose of this study was to find out the messages contained in the shadow puppet show at Padepokn Sehat Medika, Kebumen Regency. The researcher tried to examine the meaning of the message from one of the stories in the shadow puppet show at Padepokan Sehat Medika, Kebumen Regency, namely Wahyu Tejaningrat with a focus on the meaning contained in the story. The research paradigm used is constructivism, with qualitative methods and content analysis approaches. The theory used is Paul Ricoeur's Hermeneutics model where the theory is a theory regarding the rules of interpreting certain texts, signs, or symbols that have the essence of meaning. The researcher found that the story has a deep message about leadership and the role of the society in government that can educate and make people aware about the condition that happen now in society.